Matrix computations on systolic-type meshes: an introduction to the multimesh graph method - Moreno, J.H.; Lang, T. (Computer (Long Beach, Calif.), 1990)
Systolic-type arrays use both the fine-grain parallelism and the regularity of matrix computations effectively. The multimesh graph method for deriving these arrays is systematic, flexible, and easy to use.< >